Entre pontes e cidades : um estudo sobre arte, memória e paisagem urbana a partir da obra ''caminho das águas'', de Piatan Lube - Gonzalez, Vinicius Martins (2015)
This dissertation has as objective research / understand / reveal how multiple art relations with the city collaborate in the production of works capable of activating new urban landscapes by passerby. To bring the reflection as an example the work "Camin